Breaking the deadlock: A study on the pathway and effects of reshaping the sustainable marketing capability of Chinese time-honored brands. - Xiangyu Li; Danaikrit Inthurit; MaoChun Wu; Linjun Qiu (PLoS ONE)
Numerous Chinese Time-Honored Brands are facing decline due to their limited ability to adapt to rapidly changing environments. This study identifies the core barrier as a lack of focus on developing Sustainable Marketing Capability (SMC) within the firms that own these brands. While prior research has examined the link between general marketing capabilities and corporate performance, limited attention has been paid to SMC and its effects. To address this gap, we investigated both the antecedents and outcomes of SMC. Drawing on survey data from managers and selected employees at 47 heritage enterprises in Southwest China, all of which own China Time-Honored Brands, our findings reveal that ambidextrous marketing-comprising proactive marketing exploration and exploitation-significantly enhances SMC. In turn, SMC positively impacts corporate performance and mediates the relationship between ambidextrous marketing and performance by strengthening firms' responsiveness to market and policy conditions. This study provides actionable strategies for heritage enterprises seeking to build sustainable marketing capabilities and offers practical insights into maintaining competitiveness and achieving long-term success.